2015
DOI: 10.1021/jp511575y
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Investigations of Chirality in Trimetallic Alloy Clusters: AlMnAun (n = 1–7)

Abstract: Chirality, also called handedness, plays a crucial role in function ranging from biological self-assembly schemes, organic polymer functionalities, to optical material designs. In this Article, we demonstrated a first-principles investigation of chirality in magnetic AlMnAun(0/+1/-1) (n = 1-7) clusters. Optimized structures of the AlMnAun clusters exhibit configurational combinations between AlAun+1 and MnAun+1 clusters, indicating a subtle but equal competition between Au-Al and Au-Mn interactions in the allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 113 publications
1
14
0
Order By: Relevance
“…The face substituted system is most stable, followed by the edge (0.25 eV higher) and corner (0.64 eV higher) substitutions. The same result is found in the study of Tam et al 12 In Table 2, we further list the relative energies of the NEVPT2 calculations, using (c)-CAS (11,10), which support the energetic order of the B3LYP calculations. For most systems however, NEVPT2 predicts slightly higher relative energies.…”
Section: Au 18 Fe and Au 19 Festabilitiessupporting
confidence: 81%
See 3 more Smart Citations
“…The face substituted system is most stable, followed by the edge (0.25 eV higher) and corner (0.64 eV higher) substitutions. The same result is found in the study of Tam et al 12 In Table 2, we further list the relative energies of the NEVPT2 calculations, using (c)-CAS (11,10), which support the energetic order of the B3LYP calculations. For most systems however, NEVPT2 predicts slightly higher relative energies.…”
Section: Au 18 Fe and Au 19 Festabilitiessupporting
confidence: 81%
“…[2][3][4][5][6][7] Gold clusters usually exhibit small (S ¼ 0, 1/2) spin quantum numbers, leading to closed shell or doublet electronic ground states but doping them with a transition metal atom can lead to open-shell clusters with signicantly higher spin-quantum numbers. [8][9][10][11][12][13][14] For example, Tam et al 12 investigated the structure and stability of transition metal doped golden pyramids Au 19 M (M ¼ Cr, Mn, Fe) at the level of generalized gradient density functional theory (DFT). All systems show higher ground state spin quantum numbers, while the structural modications are minor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When clusters or atoms contact the substrate, physical or chemical adsorptions occur due to the interaction schemes and kinetic energies of the 0D objects [49]. Along with tailored optic and electronic properties [50], the guest clusters are endowed with tunable magnetism and chemical reactivity [51,52], which allows them to act as essential building bricks for functional nanomaterials [53]. A previous doping strategy showed that replacing both the Mo and S atoms with FeX 6 (X = S, C, N, O, F) clusters allowed for intrinsic ferromagnetism to be brought into the cluster-doped stable slabs [54].…”
Section: Introductionmentioning
confidence: 99%